Pro-Social Behavior, Reciprocity or Both? - Bruno S. Frey; Stephan Meier (Center for Economic Studies and ifo Institute (CESifo), 2002)
Empirical evidence is provided for the importance of non-reciprocal pro-social behavior of individuals in an anonymous, n-person pure public good setting. A unique panel data set of 136,000 observations is matched with an extensive survey. Even under anonymous conditions, a large number of individuals are prepared to donate quite a significant sum of money. Cooperation conditional on giving by specific other persons (reciprocity) is present, but the causal relationship is ambiguous. The manner in which one is asked to donate is crucial. Identification with the organization is also important.
Keywords: 330; public goods; pro-social behavior; reciprocity; donation